Analisis Risiko Pada Usaha Mebel Menggunakan House of Risk - Rubik, Filimon Erno; Alfani, Musaddad (Universitas Muhammadiyah Sorong, 2025)
The furniture industry is one of the manufacturing sectors that makes a significant contribution to the economy. However, the complexity of the production process, ranging from raw material procurement to product distribution, makes this industry vulnerable to various internal and external risks. If not properly managed, these risks may hinder production targets, reduce product quality, and weaken the company’s competitiveness. This study aims to identify and design risk mitigation strategies in a furniture business in Yogyakarta using the House of Risk (HoR) method. Data were collected through observation and questionnaires to assess risk events and risk agents. The HoR phase 1 analysis identified nine risk events and twenty-two risk agents, with five priority risk agents, namely raw material shortages due to poor planning, suboptimal maintenance, limited raw material stock from suppliers, delays in machine spare parts procurement, and lack of worker skills. Subsequently, HoR phase 2 produced five main mitigation strategies, including improving raw material requirement calculations, establishing clear maintenance schedules, expanding supplier networks, enhancing interdepartmental coordination, and providing worker training and certification. The findings indicate that the application of the HoR method can assist furniture companies in prioritizing risk sources and formulating more systematic and targeted mitigation strategies.